CYP1A2 genotype and the ergogenic effect of acute caffeine intake on muscular strength and endurance performance in trained individuals - Montalvo-Alonso, J. J.; del Val-Manzano, M.; Martín-Rivas, I.; Ferragut, C.; Valadés, D.; Pérez-López, A. (Scandinavian Journal of Medicine & Science in Sports, 2026)
This study examined whether CYP1A2 (rs762551) genotype modulates the acute ergogenic effects of caffeine on muscular strength and endurance performance in resistance-trained men and women. Ninety-four resistance-trained participants (47 females, 47 males; 39 AA, 44 AC, 11 CC) completed a randomized, triple-blind, placebo-controlled, crossover trial. Participants ingested 3 mg/kg of caffeine or placebo before performing standardized bench press and back squat tests. Mean velocity was measured to assess strength performance against different loads (25%-90%) and muscular endurance during a single set performed to failure at 65% 1RM. Data were analyzed using ANCOVA with supplement, genotype, and sex as factors. Caffeine significantly improved strength and endurance performance across conditions (p < 0.01, Eta2p = 0.077-0.294). Mean velocity increased by 4%-12% in AA and 3%-9% in AC individuals, particularly at 50%-90% 1RM, whereas CC carriers showed minor changes (<= 4%). Supplement by genotype interaction was noted only at 90% 1RM in mean velocity (p < 0.05, Eta2p = 0.094). In the muscular endurance test, mean velocity improved by 4%-6% in AA, 3%-4% in AC, and 2%-6% in CC. No sex differences or ergolytic effects were observed. Acute ingestion of 3 mg/kg caffeine enhances strength and endurance performance in resistance-trained men and women. Although CYP1A2 genotype did not alter the overall effect, benefits were greatest in AA, intermediate in AC, and minimal in CC carriers. These findings support low-dose caffeine as an effective and safe ergogenic aid in resistance training regardless of sex, with individual variability partly explained by genotype.